The accidental princess - Storer, Jen 1961- (Puffin Books, 2016)
Inside the lilac hedge, two sets of glittering emerald eyes observed Matilda through the heart-shaped leaves. 'It is the princess!' whispered a tiny voice . . . When the pixies and fairies of the lilac hedge mistake Matilda for royalty, she is drawn into a wondrous world. But evil forces threaten the hedge and its folk, and Matilda must fight to save her new friends. She can't do it alone, but could it mean losing her sister forever?